Metode Menghafal Al-Qur’an di Yayasan Tahfidz Qur’an Al-Husna Sei Kepayang - Arlina Arlina; Muhammad Syah Bagus; Miftah Ilham Mazid; Asmadi Limbong; Elda Arzetin Elsil (Journal on Education, 2023)
This study aims to analyze the method of memorizing the Qur’an YTQ al-husna Sei kepayang to foster Islamic religious education in the village. The focus of the Qur’an memorization method is the form of effort, supporting factors, and obstacles. This study analyzed the efforts made by UINSU students in Sei kepayang, Sei Kepayang district, east of Asahan Regency, North Sumatra. The research method used is qualitative based on descriptive studies. The data collection techniques used are observation, interviews, and documentation studies. The data that was proleh was then analyzed using Miles and Huberman's techniques, namely data reduction, data display, and drawing conclusions. The results of the study explained that the form of efforts made was to include children in non-formal religious education, foster children's religious practice at YTQ al-husna and be useful at home, and participate in diversity traditions based on local wisdom, getting children to grow up in surau. The supporting factors for the implementation of these efforts are the high motivation and expectations of parents for their children's education, besides being supported by a religious village environment. The inhibiting factor is that the busyness of parents at work is an obstacle to not being able to fully control the child's religious development.